(untitled) (Communications in Computational Physics, 2023)
In this paper, we discuss the conforming finite element method for a modified interior transmission eigenvalues problem. We present a complete theoretical analysis for the method, including the a priori and a posteriori error estimates. The theoretical analysis is conducted under the assumption of low regularity on the solution. We prove the reliability and efficiency of the a posteriori error estimators for eigenfunctions up to higher order terms, and we also analyze the reliability of estimators for eigenvalues. Finally, we report numerical experiments to show that our posteriori error estimator is effective and the approximations can reach the optimal convergence order. The numerical results also indicate that the conforming finite element eigenvalues approximate the exact ones from below, and there exists a monotonic relationship between the conforming finite element eigenvalues and the refractive index through numerical experiments.